Unraveling the impact of frailty on postoperative delirium in elderly surgical patients: a systematic review and meta-analysis - Haotian Wu; Siyi Yan; Han Cao; Chunyu Feng; Huan Zhang (BMC Anesthesiology)
Abstract Background Frailty has been consistently implicated as a pivotal factor in the onset of delirium following anesthesia and surgery. Nonetheless, a comprehensive understanding of the relationship between frailty and delirium remains to be elucidated. This study addresses that knowledge gap. Methods A comprehensive search of literature databases identified 43 relevant studies involving 14,441 participants. The studies were subjected to a rigorous quality assessment using the Newcastle-Ottawa Scale. Statistical analysis was conducted using Review Manager (v5.4.1), including subgroup and sensitivity analyses. Results Meta-analysis revealed a significant association between preoperative physical frailty and postoperative delirium (pooled odds ratio: 2.47; 95% confidence interval: 2.04–2.99; I 2 = 46.7%). The baseline frailty rate was 34.0% (4,910/14,441), while the overall incidence of postoperative delirium was 20% (2,783/14,441). Subgroup analyses based on characteristics such as race, frailty-assessment tools, and surgical types were conducted to explore potential sources of heterogeneity. This meta-analysis provided compelling evidence supporting a notable link between preoperative physical frailty and an increased risk of postoperative delirium in older surgical patients. Early identification through frailty screening can enable targeted interventions, potentially enhancing overall management and individualized treatment. Integrating frailty assessment into preoperative evaluation may improve predictive accuracy in surgical planning and anesthesia management. Conclusions Future research could focus on optimizing the integration of frailty assessment into preoperative protocols for timely intervention and improved patient outcomes. Trial registration The review protocol was registered with PROSPERO (CRD42023390486), date of registration: Aug 11, 2023.